RELEVANSI INFORMASI KINERJA KEUANGAN TERHADAP RESPON INVESTOR PADA PERUSAHAAN SEKTOR BARANG KONSUMEN NON-PRIMER DI INDONESIA - Silaban, Christo Gusnandar; Murti, Nugroho Wisnu (STIE Semarang, 2024)
The issue of accounting information's losing significance internationally, particularly in determining the utility of accounting information generated from financial statements, is one that requires attention in Indonesia. This focus originates from the practical reality that domestic investors continue to prioritize financial performance, with financial reports serving as their primary source of information. The purpose of this research is to assess the relevance of financial performance information based on earnings per share and accounting-based measures (i.e., current ratio, net profit margin, and return on equity) to investor responses. The observation focused on stock trading operations in Indonesia's secondary market for consumer cyclicals sector. The observation concentrated on stock trading activity in Indonesia's secondary market for non-primary sector companies. The sector is more vulnerable to technological innovation than other sectors. The investigation was conducted on companies with longitudinal data, especially 50 companies from 2019 to 2023. The analysis tool can be utilized to do panel data regression on a balanced sample of data. The research showed that investors respond immediately to current ratio information (p-value < 0.05). However, the research found that profit-based performance information (i.e., net profit margin and return on equity) has no significant influence on investor response (p-value > 0.05). These results show that investors in sectors considered to be more responsive to innovation are more interested in information about firm assets that can predict future performance than profit information, which is more historical. This is supported by the fact that market-based performance information (i.e., earnings per share) receives immediate and considerable attention from investors. This study is intended to serve as a reference for future value relevance studies in more particular areas. Upcoming research should also consider economic situations, which can be incorporated into the analysis model to assess the coherence of the research conclusions.